Prostitution and the Ideal State: A Defense of a Policy of Vigilance - Vicente, Agustin (Ethical theory and moral practice, 2016)
The debate concerning prostitution is centered around two main views: the liberal view and the radical feminist view. The typical liberal view is associated with decriminalization and normalization of prostitution; radical feminism stands in favor of prohibition or abolition. Here, I argue that neither of the views is right. My argument does not depend on the plausible (or actual) side effects of prohibition, abolition, or normalization; rather, I am concerned with the ideals involved. I will concede to liberals their claim that prostitution is not harmful in itself. Yet, I will argue that prostitution cannot be thought of as just another job. Even if prostitution is not harmful in itself, it can do much harm. I will argue that a policy of vigilance is the most adequate one to adopt with regard of prostitution, given the risk of harm associated with prostitution. A policy of vigilance tries to discriminate between those who take a certain course of action willingly and those who do not. It puts no restraints on those who exercise their genuine will, but protects those who are openly or subtly coerced.